1981
DOI: 10.1002/ardp.19813141109
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen an 1,3‐Dicarbonyl‐Verbindungen, 18. Mitt. 2,4‐Diaryl‐6‐methyl‐1,2,3,4‐tetrahydropyrimidin‐5‐carbon‐säureester

Abstract: Bei der Hanrzsch-Synthese werden neben den 1,4-Dihydropyridinen 1 die diastereomeren 1,2,3,4-Tetrahydropyrimidine 2 und 3 erhalten. Die Titelverbindungen werden zu den Pynmidinen 7 oxidiert. Photolyse von Id liefert das Dimer 10. k, M und k, 3d werden photochemisch zu den Bisnitrosophenylpyrimidinen 11 umgesetzt. Unter reduktiven Bedingungen werden aus k die Abbauprodukte 12 und l3 isoliert.In addition to the 1,4-dihydropyridines 1, the diastereomeric 1,2,3,4-tetrahydropyrimidines 2 and 3 are obtained by Hanfz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Ethyl 4-Methyl-2,6-diphenylpyrimidine-5-carboxylate (3a): [23] White solid; m.p. and PPh 3 (52.5 mg, 0.20 equiv.)…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ethyl 4-Methyl-2,6-diphenylpyrimidine-5-carboxylate (3a): [23] White solid; m.p. and PPh 3 (52.5 mg, 0.20 equiv.)…”
Section: Methodsmentioning
confidence: 99%
“…To our delight, the C-C cross-coupling product 3a was isolated in 80 % yield (entry 5). We also examined several pyridin-2-yl sulfonates, including pyridin-2-yl sulfonate (1g), and 5-bromo-, 5-methyl-and 5-nitro substituted pyridin-2-yl sulfonates (1h-j) as substrates in the Suzuki-Miyaura coupling reaction with four arylboronic acids ( Table 2, entries [17][18][19][20][21][22][23][24][25][26]. This revealed that the reaction was best conducted with 5 mol-% Pd(OAc) 2 as the catalyst and either 20 mol-% PPh 3 or 6 mol-% 2,2Ј-oxybis(2,1-phenylene)bis(diphenylphos-phane) (DPE-Phos) as ligand, and 2.5 equivalents of K 3 PO 4 as base, 1,4-dioxane as solvent at 110°C for 7 h, which afforded the desired product in an isolated yield of 86 or 87 %, respectively (entries 4-9).…”
Section: Coupling Reaction Of Pyrimidin/pyridin-2-yl Sulfonates With mentioning
confidence: 99%
See 2 more Smart Citations
“…If one would assume that dinitration of DHPM 1 at 50 °C (60% HNO 3 ) leads to gemdinitro pyrimidone B/C, an internal redox process would readily furnish nitrolic acid 5. Although there is literature precedent for the gem-dinitration of active methylene and methyl groups [8,[35][36][37], we are not aware of any precedent for a (non-photochemical [38][39][40][41]) redox process such as the hypothetical C → H transformation.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%